Quantitation of the A2A Adenosine Receptor Density in the Striatum of Mice and Pigs with [18F]FLUDA by Positron Emission Tomography - Daniel Gündel; Magali Toussaint; Thu Hang Lai; Winnie Deuther-Conrad; Paul Cumming; Susann Schröder; Rodrigo Teodoro; Rareş-Petru Moldovan; Francisco Pan-Montojo; Bernhard Sattler; Klaus Kopka; Osama Sabri; et al. (MDPI AG, 2022)
The cerebral expression of the A2A adenosine receptor (A2AAR) is altered in neurodegenerative diseases such as Parkinson's (PD) and Huntington's (HD) diseases, making these receptors an attractive diagnostic and therapeutic target. We aimed to further investigate the pharmacokinetic properties in the brain of our recently developed A2AAR-specific antagonist radiotracer [18F]FLUDA. For this purpose, we retrospectively analysed dynamic PET studies of healthy mice and rotenone-treated mice, and conducted dynamic PET studies with healthy pigs. We performed analysis of mouse brain time-activity curves to calculate the mean residence time (MRT) by non-compartmental analysis, and the binding potential (BPND) of [18F]FLUDA using the simplified reference tissue model (SRTM). For the pig studies, we performed a Logan graphical analysis to calculate the radiotracer distribution volume (VT) at baseline and under blocking conditions with tozadenant. The MRT of [18F]FLUDA in the striatum of mice was decreased by 30% after treatment with the A2AAR antagonist istradefylline. Mouse results showed the highest BPND (3.9 to 5.9) in the striatum. SRTM analysis showed a 20% lower A2AAR availability in the rotenone-treated mice compared to the control-aged group. Tozadenant treatment significantly decreased the VT (14.6 vs. 8.5 mL · g−1) and BPND values (1.3 vs. 0.3) in pig striatum. This study confirms the target specificity and a high BPND of [18F]FLUDA in the striatum. We conclude that [18F]FLUDA is a suitable tool for the non-invasive quantitation of altered A2AAR expression in neurodegenerative diseases such as PD and HD, by PET.